2005
DOI: 10.1111/j.1439-0523.2005.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping antixenosis genes on chromosome 6A of wheat to greenbug and to a new biotype of Russian wheat aphid

Abstract: Greenbug and Russian wheat aphid (RWA) are two devastating pests of wheat. The first has a long history of new biotype emergence and recently. RWA resistance has just started to break down. Thus, it is necessary to find new sources of resistance that will broaden the genetic base against these pests in wheat. Seventy‐five doubled haploid recombinant (DHR) lines for chromosome 6A from the F1 of the cross between “Chinese Spring’ and the “Chinese Spring (Synthetic 6A) (Triticum dicoccoides × Aegilops tauschii)” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
(10 reference statements)
0
25
0
1
Order By: Relevance
“…Moreover, adapta-tion to higher levels of hydroxamic acids could evolve in aphids since they can produce several generations in a short period of time. For instance, a new biotype of the Russian wheat aphid, Diuraphis noxia, was able to break down the resistance of wheat varieties released previously (Castro et al 2005) and, for other plant species too, some resistancebreaking aphid biotypes have been discovered (Dogimont et al 2010). Plants showing different concentrations of hydroxamic acids were able to generate genotypic differences in S. avenae after just a few generations (Figueroa et al 2002) and the assessment of the genetic variability and population structure of S. avenae, collected in Chile, has revealed that some aphid genotypes show highest performance on plants with the highest concentration of hydroxamic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adapta-tion to higher levels of hydroxamic acids could evolve in aphids since they can produce several generations in a short period of time. For instance, a new biotype of the Russian wheat aphid, Diuraphis noxia, was able to break down the resistance of wheat varieties released previously (Castro et al 2005) and, for other plant species too, some resistancebreaking aphid biotypes have been discovered (Dogimont et al 2010). Plants showing different concentrations of hydroxamic acids were able to generate genotypic differences in S. avenae after just a few generations (Figueroa et al 2002) and the assessment of the genetic variability and population structure of S. avenae, collected in Chile, has revealed that some aphid genotypes show highest performance on plants with the highest concentration of hydroxamic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Two QTLs explaining antixenotic resistance against greenbug and RWA were mapped in the same DHR population (Castro et al 2005) close to the regions identiWed with the present hormone treatments. In addition, a QTL providing resistance against Mycosphaerella graminicola (Stb15) has been mapped in the same region of 6AS of the cultivar 'Arina' (Arraiano et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The construction of the map was described in Castro et al (2005). QTL mapping of the traits was performed using QGENE software (Nelson 1997).…”
Section: Qtl Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is speculated that the Dn genes conferring RWA resistance located on wheat chromosome 7DS form a linkage group consisting of Dn1 , Dn2 , Dn5 and Dnx , while Dn9 is located in a defense-gene-rich region of wheat chromosome 1DL (Lui et al 2001(Lui et al , 2002(Lui et al , 2005. However, a quantitative trait locus (QTL), which accounted for most of the antixenosis against RWA that appeared in Argentina in 2003, was mapped to chromosome 6A (Castro et al 2005).…”
Section: Candidate R-genes For Rwa Resistancementioning
confidence: 99%